Rekonstruksi Konsep Waktu Shalat: Sintesis Al-Qur’an dan Hadis serta Relevansinya di Lingkungan Kementerian Agama - Siti Mutiah Btr; Marlina; Ahmad Safani; Ahmad Fauzi; Torkis Rangkuti; Parlindungan (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
Prayer times constitute a fundamental component of Islamic worship, serving as a prerequisite for the validity of prayer performance. The determination of prayer times is rooted in the Qur’an and Hadith, which provide both normative principles and practical guidance. In the context of modern society, characterized by scientific advancement and technological development, a deeper conceptual understanding of prayer times is required to ensure their continued relevance. This study aims to examine and reconstruct the concept of prayer times from the perspectives of the Qur’an and Hadith, while exploring its relevance within contemporary religious practices. Employing a qualitative approach, this research adopts a library research method. The data were collected through an in-depth examination of Qur’anic verses and Prophetic traditions related to prayer times, supported by secondary sources such as Qur’anic exegesis, hadith commentaries, and relevant academic publications. Data analysis was conducted using thematic and descriptive-analytical approaches. The findings reveal that the concept of prayer times in Islamic primary sources is governed by clear normative boundaries, while simultaneously allowing contextual flexibility. This reconstruction underscores the necessity of integrating textual fidelity with contextual understanding in order to maintain the continuity and applicability of Islamic teachings in a changing era